Pigs are not susceptible to SARS‐CoV‐2 infection but are a model for viral immunogenicity studies. Issue 4 (23rd October 2020) - Vergara‐Alert, Júlia; Rodon, Jordi; Carrillo, Jorge; Te, Nigeer; Izquierdo‐Useros, Nuria; Rodríguez de la Concepción, María Luisa; Ávila‐Nieto, Carlos; Guallar, Víctor; Valencia, Alfonso; Cantero, Guillermo; Blanco, Julià; Clotet, Bonaventura; et al.
Abstract: Conventional piglets were inoculated with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) through different routes, including intranasal, intratracheal, intramuscular and intravenous ones. Although piglets were not susceptible to SARS‐CoV‐2 and lacked lesions or viral RNA in tissues/swabs, seroconversion was observed in pigs inoculated parenterally (intramuscularly or intravenously).